Moses and the Deuteronomic prophetic ideal as interpreted through the Elijah-Elisha narratives - Capulong, Noriel C. (Dumaguete City Silliman University, 1987)
This dissertation is primarily an examination of the Elijah-Elisha stories as the prophetic voices behind their composition reinterpret and reappropriate the Mosaic prophetic tradition found in the book of Deuteronomy. Secondarily, this work attempts to interpret contemporary Philippine situation in the light of the examined biblical texts
Dr. Rowland D. Van Es (Adviser)
A dissertation submitted to the South East Asia Gradutate School of Theology in compliance with the requirements for the Doctor of Theology (S.E.A.) degree program
Thesis (D. Theo.)- South East Asia Graduate School of Theology
Keywords: Bible -- O.T. -- Deuteronomy -- Criticism, interpretation, etc